2019
DOI: 10.33062/ajb.v2i02.101
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CREDIT RISK AND CAPITAL ADEQUACY RATIO UPON RETURN ON ASSET (A Case Study at Banking Listed in Indonesia Stock Exchange)

Abstract: The aim of study to examine the effect of credit risk as measured by non performing loan, and capital adequacy ratio to profitability level measured by return on assets in banking companies listed in Indonesia Stock Exchange (IDX). This research belongs to causative research. The population in this study is the stateowned banks listed on Indonesia Stock Exchange. The sample of this study is determined by purposive sampling method so that obtained four sample companies. The type of data used is secondary data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 0 publications
2
16
0
10
Order By: Relevance
“…Asset (I2) is the bank's entire property, including cash, demand deposits with Bank Indonesia, placements with other banks, securities held, financing or credit, and fixed assets. According to (Hanafi, et al, 2007) assets are economic benefits to be received in the future or controlled by the bank due to a transaction or event (Anwar & Murwaningsar, 2017), there is a positive and significant influence between assets and the number of credits. With high asset value, the bank will improve the capital structure to warrant the risk of placement of productive assets, including credit/financing, to make a profit from the investment activities (Purwanto, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Asset (I2) is the bank's entire property, including cash, demand deposits with Bank Indonesia, placements with other banks, securities held, financing or credit, and fixed assets. According to (Hanafi, et al, 2007) assets are economic benefits to be received in the future or controlled by the bank due to a transaction or event (Anwar & Murwaningsar, 2017), there is a positive and significant influence between assets and the number of credits. With high asset value, the bank will improve the capital structure to warrant the risk of placement of productive assets, including credit/financing, to make a profit from the investment activities (Purwanto, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in assessing capital adequacy, the Bank must also link capital adequacy with bank risk profiles. Anwar & Murwaningsari (2017), and Olaruntoba et al (2018) show that CAR has a positive impact on profitability.…”
Section: Figurementioning
confidence: 96%
“…This research aims to describe the financial performance of the bank based on the output. Anwar, Y and Murwaningsari, E (2016), revealed that credit risk as measured by non-performing loan (NPL) has a significant influence on profitability in the banking industry listed on the Indonesia Stock Exchange (IDX).…”
Section: Background Of the Researchmentioning
confidence: 99%